2007
DOI: 10.1186/1471-2229-7-13
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the rapid expansion of microRNA-mediated regulation in early land plant evolution

Abstract: BackgroundMicroRNAs (miRNAs) are regulatory RNA molecules that are specified by their mode of action, the structure of primary transcripts, and their typical size of 20–24 nucleotides. Frequently, not only single miRNAs but whole families of closely related miRNAs have been found in animals and plants. Some families are widely conserved among different plant taxa. Hence, it is evident that these conserved miRNAs are of ancient origin and indicate essential functions that have been preserved over long evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 76 publications
6
92
0
1
Order By: Relevance
“…At least 88 annotated miRNA families have been identified in the moss P. patens and 44 in the lycopod Selaginella moellendorffii (Axtell et al, 2007;Fattash et al, 2007). The target analysis indicates that in P. patens several miRNAs regulate overall development and are involved in signal transduction, cell wall biosynthesis and defense pathways.…”
Section: Bryophytes As An Ancient Lineage May Have Retained Many Novementioning
confidence: 99%
“…At least 88 annotated miRNA families have been identified in the moss P. patens and 44 in the lycopod Selaginella moellendorffii (Axtell et al, 2007;Fattash et al, 2007). The target analysis indicates that in P. patens several miRNAs regulate overall development and are involved in signal transduction, cell wall biosynthesis and defense pathways.…”
Section: Bryophytes As An Ancient Lineage May Have Retained Many Novementioning
confidence: 99%
“…Direct sequencing of small RNAs and computational predictions have resulted in the annotation of 44 distinct P. patens miRNA families (Arazi et al, 2005;Talmor-Neiman et al, 2006a;Fattash et al, 2007). We have recently reported a data set of 127,135 unique P. patens small RNAs from three libraries, represented by a total of 561,102 reads, which provided insights into siRNA biogenesis in plants .…”
Section: Identification Of Mirnas From P Patens and S Moellendorffiimentioning
confidence: 99%
“…To date, >40 distinct miRNA families have been annotated from P. patens based upon analysis of sequenced small RNAs or bioinformatic predictions (Arazi et al, 2005;Talmor-Neiman et al, 2006a;Fattash et al, 2007). In lycopods, the expression of miR166 has been confirmed in S. moellendorffii (Floyd and Bowman, 2004), and the expression of two additional families proposed based upon microarray experiments using RNA from Selaginella uncinata (Axtell and Bartel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…7,[9][10][11][12] The evolution of such nonconserved miRNAs could have reshaped gene networks during the history of the diversification of plants to promote the development of novel, derived characteristics. Mechanistically, it has been shown that miRNAs can evolve de novo from tandem gene duplicates that are inverted relative to each other and that such miRNAs can subsequently target their progenitors by sequence similarity.…”
mentioning
confidence: 99%